Performance study of path loss models for LTE-A relay stations - Mansor, Mohamad ‘Ismat Hafizi; Mohd. Ramli, Huda Adibah (Institute of Electrical and Electronics Engineers Inc., 2016)
Relaying technology (i.e. relay network) is one of the technologies that plays a significant role for improving the performance of an emerging wireless communication standard known as, Long Term Evolution-Advanced (LTE-A). Backhaul link is one of the links in the relay networks that is responsible for data communication between base station and relay stations. To ensure efficient communication in the backhaul link, good radio propagation environment, such as path loss, is required. This paper evaluates the performance of a number of well-known path loss models (original and modified versions) in order to identify the most suitable model for usage in backhaul link of LTE-A relay station. The results demonstrate that the modified COST231-Hata model which is introduced with some modifications is the most suitable for implementation in the backhaul link of LTE-A relay station.